Muscle activation in the main muscle groups of the lower limbs in high-level dancesport athletes - Liébana, E.; Monleón, C.; Morales, R.; Pablos, C.; Moratal, C.; Blasco, E. (Medical problems of performing artists, 2018)
Dancers are subjected to high-intensity workouts when they practice dancesport, and according to the literature, they are prone to injury, primarily of the lower limbs. The purpose of this study was to determine whether differences exist in relative activation amplitudes for dancers involved in dancesport due to muscle, gender, and type of dance. Measurements were carried out using surface electromyography equipment during the choreography of a performance in the following leg muscles: rectus femoris, biceps femoris, tibialis anterior, and gastrocnemius medialis. Eight couples of active dancesport athletes (aged 20.50±2.75 yrs) were analyzed. Significant gender differences were found in rumba in the tibialis anterior (p<0.05) and gastrocnemius medialis (p<0.05). Based on the different activations, it is possible to establish possible mechanisms of injury, as well as tools for preventing injuries and improving sports performance.